Telehealth for children and adolescents with chronic pulmonary disease: systematic review - Adriana Virgínia Barros Faiçal; Laís Ribeiro Mota; Danilo d' Afonseca Correia; Larissa Prazeres Monteiro; Edna Lúcia de Souza; Regina Terse-Ramos (Sociedade de Pediatria de São Paulo, 2023)
Abstract Objective: To revise the impact of telehealth on the quality of life, reduction in pulmonary exacerbations, number of days using antibiotics, adherence to treatment, pulmonary function, emergency visits, hospitalizations, and the nutritional status of individuals with asthma and cystic fibrosis. Data source: Four databases were used, MEDLINE, LILACS, Web of Science and Cochrane, as well as manual searches in English, Portuguese and Spanish. Randomized clinical trials, published between January 2010 and December 2020, with participants aged 0 to 20 years, were included. Data synthesis: Seventy-one records were identified after the removal of duplicates; however, twelve trials were eligible for synthesis. Included trials utilized: mobile phone applications (n=5), web platforms (n= 4), mobile telemedicine unit (n=1), software with an electronic record (n=1), remote spirometer (n=1), and active video games platform (n=1). Three trials used two tools, including telephone calls. Among the different types of interventions, improvement in adherence, quality of life, and physiologic variables were observed for mobile application interventions and game platforms compared to usual care. Visits to the emergency department, unscheduled medical appointments, and hospitalizations were not reduced. There was considerable heterogeneity among studies. Conclusions: The findings suggest that better control of symptoms, quality of life, and adherence to treatment can be attributed to the technological interventions used. Nevertheless, further research is needed to compare telehealth with face-to-face care and to indicate the most effective tools in the routine care of children with chronic lung diseases.